MCC Regulator of WNT Signaling Pathway (MCC) Is a Podocyte Essential Gene - Song, Hui; Zhuang, Lulu; Xu, Xiaodong; Shi, Jingsong; Hu, Weixin; Liu, Zhihong; Shi, Shaolin (Frontiers in Medicine, 2021)
Podocytes are an integral part of the glomerular filtration barrier. Many genes are already known to be essential for podocyte survival, structure and function, but there are more podocyte essential genes to be identified. By single-cell RNA-seq of mouse podocytes, we detected the expression of gene encoding MCC regulator of WNT signaling pathway (MCC) in majority of the podocytes and speculated that MCC is essential for podocytes. We confirmed MCC expression in mouse podocytes and further showed its expression in human podocytes. To experimentally prove the essentiality of MCC for podocytes, we knocked down MCC in cultured podocytes and found marked morphological change of cell shape, cytoskeletal F-actin stress fiber disruption, increased apoptosis, and downregulation of podocyte essential genes, CD2AP and WT1, demonstrating that MCC is essential for podocytes. Since MCC has been implicated in cell cycle and β-catenin signaling, we examined the expression of cell cycle related genes and activity of β-catenin in the MCC knockdown podocytes, but did not find significant changes. To further explore the mechanism underlying the role of MCC in podocytes, we performed RNA-sequencing and bioinformatics analysis of MCC knockdown podocytes and found a significant enrichment of the regulated genes in lamellipodia formation. Consistently, we found that MCC is present in lamellipodia and MCC knockdown resulted in loss of lamellipodia in the cells. Lastly, we found that MCC was downregulated in podocytes treated with puromycin aminonucleosides and in glomeruli of diabetic mice and FSGS patients, implicating MCC is involved in the development of podocytopathy and proteinuria. In conclusion, MCC is potentially essential for podocytes and its downregulation may be involved in podocytopathy.